Does access to credit matter in land transfer decision-making? Evidence from China - Yu, Xi; Su, Qin; Lyu, Jianxing (Frontiers in Environmental Science, 2023)
Land transfer is a favorable tool to solve the low land utilization rate caused by population aging and migration. Most previous studies about land transfer behavior focus on the participation and area of transfer, while little attention was paid to farmers' future land transfer intentions. Hence, by building an analysis framework of land transfer-in “participation-area-future willingness”, this study uses the recent farm-level data from China to systematically examine the relationship between access to credit and land transfer-in decision behaviors. Considering the potential endogeneity and selection bias from the observable and unobservable factors, we employ the Endogenous switching models (ESR and ESP) for the analysis. The empirical results show that access to credit increases the expected probability of land transfer in participation and futural intension and helps to expand the land transfer in area. Specifically, access to credit contributes to increasing the participation, area and futural willingness of farmers’ land transfer in by 62.6%, 126%, and 74.9%, respectively. The positive role of access to credit is confirmed by the estimates of the PSM approach. Our findings highlight financial support by access to credit can encourage farmers’ land transfer-in behaviors and further protect the limited arable land source.